Suggestions for a Guideline for Cochlear Implantation in CHARGE Syndrome. Issue 9 (October 2016) - Vesseur, Annemarie; Free, Rolien; Langereis, Margreet; Snels, Chantal; Snik, Ad; Ravenswaaij-Arts, Conny van; Mylanus, Emmanuel
Abstract : Objective: Identifying aspects for establishing cochlear implantation guidelines for patients with ocular coloboma, heart defects, atresia of the choanae, retardation (of growth and/or of development), genital anomalies, and ear anomalies (CHARGE) syndrome (CS). Study Design: Explorative retrospective study. Setting: Cochlear implant (CI)-centers of tertiary referral centers in The Netherlands. Patients: Ten patients with CS who received a CI between 2002 and 2012. Interventions: Describing the challenges and benefits of cochlear implantation in CS. Main Outcome Measures: Imaging and surgical findings, language development, and Quality-of-life (QoL), compared with two control groups: 1) 34 non-syndromic CI-users and 2) 13 patients with CS without CI because of sufficient hearing. Results: Subjective and objective audiometry and magnetic resonance imaging were necessary to confirm the presence of the cochlear nerve. Surgery in CS was challenging because of enlarged emissary veins, semi-circular-canal aplasia, aberrant facial nerve, and dysplastic cochlear windows, making computed tomography indispensable in surgical preparations. No major intraoperative complications occurred. Despite additional handicaps, all patients showed auditory benefit and improvement in disease-specific QoL. Patients implanted at a relatively young age (⩽37 months) followed by a long period of CI-use (>5 years) and with minor additional problems, developed spoken language at a basic level comparable to that of the control group of CS patients. Conclusion: A CI should be considered in all patients with CS and severe sensorineural hearing loss. A careful work-up is required, comprising computed tomography, magnetic resonance imaging, objective, and subjective audiometry and assessment by a specialized multidisciplinary team. Cochlear implantation in CS might be complicated by syndrome-related temporal-bone anatomy, and the outcome of the CI is more individually determined. Early implantation should be aimed for. Abstract : Supplemental Digital Content is available in the text